2022
DOI: 10.1111/1440-1681.13696
|View full text |Cite
|
Sign up to set email alerts
|

Potential role of cellular senescence in pulmonary arterial hypertension

Abstract: Pulmonary arterial hypertension (PAH) is a rare and chronic lung vasculature disease characterised by pulmonary vasculature remodelling, including abnormal proliferation of pulmonary artery smooth muscle cells (PASMCs) and dysfunctional endothelial cells (ECs). Remodelling of the pulmonary vasculature occurs from maturity to senescence, and it has become apparent that cellular senescence plays a central role in the pathogenesis of various degenerative vascular diseases and pulmonary pathologies.Cellular senesc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 94 publications
0
3
0
Order By: Relevance
“…SASP is a critical marker for cellular senescence, which promotes the production of proinflammatory cytokines. 21 Proinflammatory cytokines IL‐1β and IL‐6 were significantly increased in culture supernatant of ethanol‐treated hepatocytes, while ZNF281 silence reduced the release of IL‐1β and IL‐6 under ethanol stimulation (Figure 3C,D ). Senescent hepatocytes are also featured by lipometabolic disorder.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…SASP is a critical marker for cellular senescence, which promotes the production of proinflammatory cytokines. 21 Proinflammatory cytokines IL‐1β and IL‐6 were significantly increased in culture supernatant of ethanol‐treated hepatocytes, while ZNF281 silence reduced the release of IL‐1β and IL‐6 under ethanol stimulation (Figure 3C,D ). Senescent hepatocytes are also featured by lipometabolic disorder.…”
Section: Resultsmentioning
confidence: 94%
“…Flow cytometry showed that control hepatocytes were arrested at G0/G1 phase by ethanol incubation, while ZNF281‐knockdown hepatocytes were resistant to ethanol insult, released from G0/G1 phase, and entered S phase (Figure 3B). SASP is a critical marker for cellular senescence, which promotes the production of proinflammatory cytokines 21 . Proinflammatory cytokines IL‐1β and IL‐6 were significantly increased in culture supernatant of ethanol‐treated hepatocytes, while ZNF281 silence reduced the release of IL‐1β and IL‐6 under ethanol stimulation (Figure 3C,D).…”
Section: Resultsmentioning
confidence: 96%
“…Likewise, a lower degree of perivascular lung inflammation in response to hypoxia-sugen was observed in mice with SMC-specific deletion of MR compared to wild type ( 47 ). In addition, aldosterone may exert adverse effects on PASMCs by promoting cell senescence as aldosterone has been shown as one the strong pro-senescent factors in the pathogenesis of cardiovascular diseases ( 49 ), which also play a crucial role in the pathobiology of PH ( 50 ). However, the evidence directly linking aldosterone signaling with cellular senescence in the development of PH is still lacking and should focus of the future investigation.…”
Section: Aldosterone–mr Signaling In Pulmonary Vascular Cellsmentioning
confidence: 99%